24.6k views
1 vote
Consider the system of equations.

y = –2x + 4,
3y + x = –3


Which statement is true of this system of equations?

Both equations are in slope-intercept form.

The first equation converted to slope-intercept form is y + 2x = 4.

The second equation converted to slope-intercept form is .

Neither equation is in slope-intercept form.

User Kiyomi
by
5.8k points

1 Answer

1 vote

Answer:

The second equation converted to slope-intercept form is y = (-⅓)x - 1

Explanation:

y = –2x + 4,

(In the slope intercept form)

3y + x = –3

(Not in the slope intercept form)

3y = -x - 3

y = (-⅓)x - 1

User Katiyman
by
5.5k points